PENGARUH MULTIMEDIA ARTICULATE STORYLINE BERBASIS DISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF PADA MATERI LAJU REAKSI - Nurfajriani Nurfajriani (PROSIDING SEMINAR KIMIA, 2020)
This study aims to determine differences in students' creative thinking abilities that are taught using the multimedia Learning Articulate Storyline based on Discovery Learning without using the multimedia Articulate Storyline on the reaction rate material. The sample in this study were students of MAN 3 Medan Class XI MIA 2 as Experiment Class I and Class XI MIA 4 as Experiment Class II. The instrument used was a creative thinking test instrument consisting of 4 essay questions and observation sheets. Data analysis in this study used the two-party t-test to determine differences in students' creative thinking abilities with different treatments. The results obtained are that there are differences in students' thinking ability by obtaining tcount> ttable, 5,478 > 2.021. So Ha was accepted because it was in the area of ​​rejection of Ho. Therefore, it can be concluded that there are differences in students' creative thinking abilities that are taught using the multimedia Articulate Storyline based on Discovery Learning and those who are taught multimedia Articulate Storylines. Keywords : Articulate Storyline, Discovery Learning, Multimedia, Creative Thinking